Rapid Assessment of Monovarietal Portuguese Extra Virgin Olive Oil’s (EVOO’s) Fatty Acids by Fourier-Transform Near-Infrared Spectroscopy (FT-NIRS) - Milinovic, Jelena (2019)
A rapid method for the evaluation of fatty acids (FA) of monovarietal Portuguese extra virgin olive oils (EVOOs) (n¼82) from Alentejo, southcentral region of Portugal, is developed based on Fourier-transform nearinfrared spectroscopy (FT-NIRS). The contents of FA-components (previously determined per conventional gas chromatography) are correlated with FTNIRS data (independent variable), by means of full cross-validation partial least squares regression (CVPLSR). CVPLSR is run using standard normal variate (SNV) data pre-processing and the nonlinear iterative partial least squares (NIPALS) algorithm. Obtained correlation models are characterized with good statistics: high correlation coefficients (R>0.85) and low root mean square errors (RMSE<2.04). Obtained values of the residual predictive deviation (RPD) of CVPLSR-model, higher than 5.0 (C18:1, C18:2, MUFA, PUFA) confirm the FT-NIRS as a potential method for rapid quality control of EVOO’s FA. Practical Applications: In this work for the first time, fatty acid (FA) profile of monovarietal extra virgin olive oil (EVOO) samples of the greatest olive region in Portugal—Alentejo—is analyzed by Fourier-transform near-infrared spectroscopy (FT-NIRS) and chemometrics. Obtained high-quality results allow one to recommend this technique from monitoring to quality control analysis of FA (in particular, of representative unsaturated FA), in a great number of olive oil samples, in near-real time.